Disability and work in the informal sector: consideration of inclusion and exclusion processes - Tissi, Maria Cristina (2000)
This study addressed work conditions and disability in street vendor activity in São Paulo as experience of exclusion processes and, paradoxically, of social inclusion. Work is considered by street vendors the element providing social relationships and dignity and respect in the social network, within strict limits, it also means opportunity for autonomy, decision, management of their own lives. However, as to sociability it is controversial. In respect to work process, street vendor activity shows signs of moral and political degradation. Maintenance of a corruption scheme, imposition of subordination, etc., express social exclusion, but the disabled street vendors could not be considered as excluded. It is more appropriate to consider them as closer to the vulnerability zone, characterized by occupational and relational unstability, according to Castel.